1974
DOI: 10.1107/s0567740874007953
|View full text |Cite
|
Sign up to set email alerts
|

Rubidium thiocyanate complex of 1,4,7,10,13,16-hexaoxacyclooctadecane

Abstract: Abstract. ClzH2406.RbNCS , monoclinic, P21/c, a= 11.982(6) In the latter refinement stages, the positions of the NCS atoms were held constant, the occupancy factors being allowed to vary. The final R was 0.045.t

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1974
1974
2006
2006

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…The shorter RbÀN distance (Rb1ÀN1, 3.020 (2) ) is comparable to those found in an Rb/Cr azide derivative [27] (3.010(8)-3.136 (5) ). The complex [Rb( [18]crown-6)(NCS)] 2 has also been reported, [28,29] which has six Rb À O distances (2.929-3.146 ), similar to those in the present compound, and rather symmetrical bridging thiocyanate RbÀN distances (3.314, 3.226 ), which do not show the disparity in bond lengths observed here. The structure of [Rb( [18]crown-6)(N 3 )(H 2 O)] is very similar to the known structure of [K( [18]crown-6)(N 3 )(H 2 O)], [9] but the "dimer unit" is more distorted in the potassium complex (Figure 3a).…”
Section: [K([18]crown-6)(n 3 )(H 2 O)] and [Rb([18]crown-6)(n 3 )-(H supporting
confidence: 81%
“…The shorter RbÀN distance (Rb1ÀN1, 3.020 (2) ) is comparable to those found in an Rb/Cr azide derivative [27] (3.010(8)-3.136 (5) ). The complex [Rb( [18]crown-6)(NCS)] 2 has also been reported, [28,29] which has six Rb À O distances (2.929-3.146 ), similar to those in the present compound, and rather symmetrical bridging thiocyanate RbÀN distances (3.314, 3.226 ), which do not show the disparity in bond lengths observed here. The structure of [Rb( [18]crown-6)(N 3 )(H 2 O)] is very similar to the known structure of [K( [18]crown-6)(N 3 )(H 2 O)], [9] but the "dimer unit" is more distorted in the potassium complex (Figure 3a).…”
Section: [K([18]crown-6)(n 3 )(H 2 O)] and [Rb([18]crown-6)(n 3 )-(H supporting
confidence: 81%
“…2.9 (6) H( 9) 2.8 (6) H(10) 1.8 (5) a Throughout this paper, standard deviations from the full variance-covariance matrix are given in parentheses for the least significant digit(s). 6 The form of the anisotropic temperature factor reported in Tables II and III a Atomic B's for hydrogen atoms = 5.0. The C-S-C angles average to 102.9°, less than the tetrahedral angle of 109.5°as expected.…”
Section: Methodsmentioning
confidence: 99%
“…Also one must consider that no refinement of hydrogen positions or thermal parameters was attempted here. The only other suspect distance, a long C-S distance of 1.877 Á, also involves C (6) and leads one to surmise that it is the position of C(6) which is the problem. Angles agree fairly well with those of the a molecule, and torsion angles and displacements from the S4 plane confirm the conformational similarity.…”
Section: Methodsmentioning
confidence: 99%
“…The question of macrocycle conformation in solution and the role it may play in the complexation process has been the subject of several studies.25-27 X-ray structures commonly show the uncomplexed 18c6 molecule to be in a C, conformation, while K+/18c6 is predominately [28][29][30][31][32][33][34] Theoretical studies have confirmed that the C, structure is lower in energy than D3d in the gas phase.111719 Sun and Kollman27 used free energy perturbation (FEP) calculations to obtain the relative free energies of various conformers of 18c6 in H2O. They found that the Du conformation of uncomplexed 18c6 was 5 kcal/ mol more stable than the C; conformation in H2O, consistent with interpretation of experiment.…”
Section: Introductionmentioning
confidence: 99%